Tail risk in hedge funds: A unique view from portfolio holdings - Vikas Agarwal; Stefan Ruenzi; Florian Weigert (University of Cologne, Centre for Financial Research (CFR), 2015)
We develop a new tail risk measure for hedge funds to examine the impact of tail risk on fund performance and to identify the sources of tail risk. We find that tail risk affects the cross-sectional variation in fund returns, and investments in both, tailsensitive stocks as well as options, drive tail risk. Moreover, managerial incentives and discretion as well as exposure to funding liquidity shocks are important determinants of tail risk. We find evidence that is consistent with funds being able to time tail risk exposure prior to the recent financial crisis.
Keywords: G11; G23; 330; Hedge Funds; Tail Risk; Portfolio Holdings; Funding Liquidity Risk